The effect of the DSSC photoanode area based on TiO2/Ag on the conversion efficiency of solar energy into electrical energy - Ibrayev, N.; Serikov, T.; Zavgorodniy, A.; Sadykova, A. (IOP publishing LTD, 2018)
A module based on dye-sensitized solar cells with Ag/TiO2 structure was developed. It is shown that the addition of the core-shell structure to the semiconductor film of titanium dioxide, where the nanoparticle Ag serves as the core, and the TiO2 is shell, increases the coefficient of solar energy conversion into electrical energy. The effect of the photoanode area on the efficiency of conversion of solar energy into electrical energy is studied. It is shown that the density of the photocurrentdecreases with increasing of the photoanode area, which leads to a drop in the efficiency of solar cells.